The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.2174/1874847301004010025
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of γ- Sitosterol by GC-MS from the Leaves of Girardinia heterophylla (Decne)

Abstract: Girardinia heterophylla, known as Himalayan Nettle commonly grows in temperate and subtropical Himalayas. Plant leaves were collected in winter season and analyzed using appropriate chemical methods and the biochemical constituents were ascertained. An unknown compound was isolated from leaves of the plant. After being collected, analyzed by GC-MS and compared with NIST standard chart library, it was declared to be -sitosterol, an epimer of -sitosterol.sitosterol has been reported for the first time in Girardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…Additionally, Sundarraj et al [ 16 ] demonstrated in vitro results that support the ethnomedical use of γ -sitosterol against cancer through the growth inhibition and cell cycle arrest on the apoptosis of cancer cells in accord with Endrini et al [ 17 ], which showed that γ -sitosterol was cytotoxic against colon and liver cancer cell lines and that this effect was mediated by downregulation of c-myc expression and induction of the apoptotic pathways. Currently, studies in the many plant species where γ -sitosterol is found, such as in Girardinia heterophylla [ 18 ] and Lippia nodiflora [ 14 ], agree with the four studied Lagerstroemia species, the highest level found in L. speciosa and followed by the level in L. indica . The other substances in small amounts were quoted as phytol, (Z)-9-octadecenamide (oleamide), squalene, n-hexadecanoic acid, linolenic acid, octacosane, tetratriacontane, and α -tocopherol, most of which are beneficial in humans; for examples, oleamide is a protective agent against scopolamine-induced memory loss and is suggested as useful as a chemopreventive agent against Alzheimer's disease [ 19 ], and it induces deep sleep [ 20 ] and the upregulation of appetite [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, Sundarraj et al [ 16 ] demonstrated in vitro results that support the ethnomedical use of γ -sitosterol against cancer through the growth inhibition and cell cycle arrest on the apoptosis of cancer cells in accord with Endrini et al [ 17 ], which showed that γ -sitosterol was cytotoxic against colon and liver cancer cell lines and that this effect was mediated by downregulation of c-myc expression and induction of the apoptotic pathways. Currently, studies in the many plant species where γ -sitosterol is found, such as in Girardinia heterophylla [ 18 ] and Lippia nodiflora [ 14 ], agree with the four studied Lagerstroemia species, the highest level found in L. speciosa and followed by the level in L. indica . The other substances in small amounts were quoted as phytol, (Z)-9-octadecenamide (oleamide), squalene, n-hexadecanoic acid, linolenic acid, octacosane, tetratriacontane, and α -tocopherol, most of which are beneficial in humans; for examples, oleamide is a protective agent against scopolamine-induced memory loss and is suggested as useful as a chemopreventive agent against Alzheimer's disease [ 19 ], and it induces deep sleep [ 20 ] and the upregulation of appetite [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 55%
“…Online ISSN: 2528-0422 Senyawa gamma sitosterol selain pada perlakuan I1,0K1,0 juga teridentifikasi pada perlakuan I05B0,5 dengan luas area 4,30 % dan I1,0 B1,5 dengan luas area 2,21%, luas area terbesar yaitu 14,88 % terdapat pada perlakuan I1,0K1,5. Senyawa gamma sitosterol berperan dalam mengurangi hiperglikemia dan penghambatan glikogenesis, sehingga dapat digunakan dalam pengobatan diabetes melitus, senyawa gamma sitosterol juga ditemukan pada analisis GCMS terhadap ekstrak daun Girardinia heterophylla (Tripathi, 2013). Menurut Balamurugan (2011), gamma sitosterol dapat dipertimbangkan untuk menjadi obat anti diabetic.…”
unclassified
“…[ 19 ] The γ-Sitosterol has been reported from soya which have the benefit of anti-diabetic activity. [ 20 ] And finally, the extracts of H. sabdariffa showed the presence of Hexadecanoic acid, ethyl ester which has the antioxidant and hemolytic 5-alpha reductase inhibitor feature. [ 21 ] Consequently, these compositions may be use as ingredients for the cosmetic and pharmaceutical industrials.…”
Section: Resultsmentioning
confidence: 99%